2017
DOI: 10.1186/s13031-017-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Family planning in refugee settings: findings and actions from a multi-country study

Abstract: Background: To address family planning for crisis-affected communities, in 2011 and 2012, the United Nations High Commissioner for Refugees and the Women's Refugee Commission undertook a multi-country assessment to document knowledge of family planning, beliefs and practices of refugees, and the state of service provision in the select refugee settings of Cox's Bazar, Bangladesh; Ali Addeh, Djibouti; Amman, Jordan; Eastleigh, Kenya; Kuala Lumpur, Malaysia; and Nakivale, Uganda. Methods: The studies employed mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 22 publications
6
64
1
2
Order By: Relevance
“…At the same time only 16.7% of them used a condom during the last sexual encounter. The low condom use was also documented in three other studies [16,21,27]. This also applies to other contraceptive methods.…”
Section: Resultssupporting
confidence: 69%
“…At the same time only 16.7% of them used a condom during the last sexual encounter. The low condom use was also documented in three other studies [16,21,27]. This also applies to other contraceptive methods.…”
Section: Resultssupporting
confidence: 69%
“…The contraceptive prevalence rate in our study is much lower than that of the general population of married and unmarried sexually active female adolescents in Uganda, which was reported to be 25.2% [16]. Several studies from other refugee settings have reported similar findings of low modern contraceptive use among refugee adolescents [15,22,23]. For example, in a multi country study of refugee settings, current use of contraceptives was reported to be only 4% [22].…”
Section: Discussionsupporting
confidence: 51%
“…While abortion services are available at certain private clinics, we found that financial constraints were a likely barrier for less skilled migrant women. Furthermore, the lack of information on where to obtain safe abortions and the underlying social stigma [35,[45][46][47] are plausible drivers for migrant women to seek unsafe abortions, including unregulated medical abortions.…”
Section: Discussionmentioning
confidence: 99%